SHIFTING CULTURAL VALUES IN THE MAULID PROPHET TRADITION IN BONDOWOSO - Heridianto; Muhammad zainal Abidin; Yusaul Anwar (Qolamuna : Jurnal Studi Islam, 2026)
The tradition of the Prophet's Birthday is a religious as well as a cultural expression that is full of social and spiritual values. However, modernization has given rise to a shift in the form of practice, such as food treats that used to be eaten together after Mahallul Qiyam and then closed with prayer, now replacing catering box rice that is taken home, and bherkat containing processed community products turned into matta'an store food. This phenomenon is interesting to study because it shows a shift in the value of togetherness and cultural identity. The research question is how the change in the tradition of the Prophet's Birthday is understood in the framework of local wisdom and its implications for the social, spiritual and cultural values of the community. The novelty of this research lies in the analysis of the Maulid tradition through intellectual reflection based on local wisdom. Previously, studies highlighted more aspects of ritual and history, while the aspect of shape change in the context of modernization was less considered. The research method uses a qualitative descriptive analytical approach through observation, interviews and documentation. The results of the study show that the change in the Prophet’s Birthday has an impact on three main dimensions. First, social values have been reduced because togetherness and mutual cooperation are decreasing. Second, spiritual values are maintained through prayer, prayer and Mahallul Qiyam, but tend to be individualized so that it has the potential to reduce the collective religious experience. Third, cultural values face homogenization that erodes local identity, as distinctive symbols such as Bherkat are replaced by uniform products from modern stores. This finding leads to a theoretical finding in the form of the concept of Homogenization of Religious Culture, which is when local traditions that were once full of wisdom are now standardized by modern consumption patterns (catering and manufactured products). Local uniqueness is blended into a consumptive culture that emphasizes efficiency rather than meaning. Keywords : Cultural Shift, Prophet's Birthday Tradition, Bondowoso.